2004
DOI: 10.1016/j.jim.2004.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular antibodies for proteomics

Abstract: The intracellular antibody technology has many applications for proteomics studies. The potential of intracellular antibodies for the systematic study of the proteome has been made possible by the development of new experimental strategies that allow the selection of antibodies under conditions of intracellular expression. The Intracellular Antibody Capture Technology (IACT) is an in vivo two-hybrid-based method originally developed for the selection of antibodies readily folded for ectopic expression. IACT ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 55 publications
0
62
0
Order By: Relevance
“…Antibody engineering has allowed the expression of antibody fragments intracellularly 28 and we and other researchers have shown that single variable domains of antibodies are the more efficacious intracellular antibody fragments. 29,30 There are also devised protocols for allow direct selection [31][32][33][34] (and TT & THR, in preparation). Furthermore, we have shown by X-ray crystallography, that single domains do not require intra-domain disulphide bridges to function in cells, providing the basis for single domain libraries with stable domain scaffold for selection against any antigen.…”
Section: Anti-ras Therapeutic Opportunitiesmentioning
confidence: 99%
“…Antibody engineering has allowed the expression of antibody fragments intracellularly 28 and we and other researchers have shown that single variable domains of antibodies are the more efficacious intracellular antibody fragments. 29,30 There are also devised protocols for allow direct selection [31][32][33][34] (and TT & THR, in preparation). Furthermore, we have shown by X-ray crystallography, that single domains do not require intra-domain disulphide bridges to function in cells, providing the basis for single domain libraries with stable domain scaffold for selection against any antigen.…”
Section: Anti-ras Therapeutic Opportunitiesmentioning
confidence: 99%
“…The effect of antisense technologies is often not very strong. In a number of cases, even an 80% reduction of mRNA has no effect on the phenotype caused by the protein (3). Furthermore, the interpretation of results obtained from RNAi can be complicated by the up-regulation of other genes, limitation in specificity, and induction of the interferon response (4,5).…”
mentioning
confidence: 99%
“…Antibodies are selected directly on the basis of their ability to bind antigen in vivo (60) in a modified version of the two-hybrid method for protein-protein interactions. This method allows the direct screening of yeast cells expressing antibody libraries from different sources (61)(62)(63). These "single-pot libraries of intrabodies" have greatly facilitated the selection of antibody fragments for downstream use as intrabodies in functional studies, providing a user-friendly and robust source of stable antibodies.…”
Section: Using Antibodies As Genes For Protein Silencingmentioning
confidence: 99%